2022
DOI: 10.3389/frans.2022.928573
|View full text |Cite
|
Sign up to set email alerts
|

The crux of time: A meta-analysis of ex vivo whole blood degradation

Abstract: Estimating the time since deposition (TSD) of a bloodstain can provide important medico-legal information for crime scene investigation. Research in this area primarily investigates the degradation of either hemoglobin or genetic material over time. In this work, we present a comprehensive meta-analysis on bloodstain TSD research. Our results are interpreted from 25 quantitative studies used to probe the effect of biomolecule studied, analytical technique used, substrate porosity, environmental conditions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…However, both works demonstrated that combining DNA and UV-VIS metrics generated stronger TSD models. This supports the future implementation of a combinatorial approach; rheology could be paired with a spectroscopic technique to obtain data pertaining to both DNA and protein degradation 51 .…”
Section: Moduli Values Were Above the Low-torque Limit Of The Instrum...mentioning
confidence: 57%
See 2 more Smart Citations
“…However, both works demonstrated that combining DNA and UV-VIS metrics generated stronger TSD models. This supports the future implementation of a combinatorial approach; rheology could be paired with a spectroscopic technique to obtain data pertaining to both DNA and protein degradation 51 .…”
Section: Moduli Values Were Above the Low-torque Limit Of The Instrum...mentioning
confidence: 57%
“…ACD-A was made by dissolving 0.8550 g of dextrose anhydrous, 0.8448 g of sodium citric dextrose, and 0.3072 g of citric acid, all purchased from Sigma-Aldrich (Oakville, ON), to 62.5 mL of Milli-Page|7 Q® water. RNA extracted from bovine blood with and without anticoagulant has shown no significant differences in concentration or quality metrics over time, suggesting that nucleic acid extraction can be successfully performed using anticoagulated bovine blood 49 ; it has also demonstrated utility in other TSD experiments 50,51 . Bovine blood appears to have superior erythrocyte properties than other blood analogues 50,51 .…”
Section: Blood Sample Collection and Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Current studies that develop predictive models for TSD typically use single drop or small volume (on the scale of µL) bloodstains. [6][7][8][9] There are many types of bloodstain patterns, we aim to explore the utility of select TSD methods to larger blood pools with different formation mechanics. 10 Whole blood is a colloidal suspension composed of solid cellular components (∼45% by volume) suspended in liquid (∼55% by volume).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Current studies that develop predictive models for TSD typically use single drop or small volume (on the scale of μL) bloodstains. 6–9 There are many types of bloodstain patterns, we aim to explore the utility of select TSD methods to larger blood pools with different formation mechanics. 10…”
Section: Introductionmentioning
confidence: 99%